PENGARUH AKUPRESUR TERHADAP DISMENORE PADA REMAJA: LITERATURE REVIEW - Kayla Ainayah Ramadhani; Merida Simanjuntak (AKPER Pasar Rebo, 2025)
Dysmenorrhea is a physical disorder in women during menstruation characterized by pain before or during menstruation for a short duration. It usually occurs in the lower abdomen or pelvis and is often accompanied by muscle cramps. This condition is commonly experienced by teenage girls and if untreated, it can interfere with activities and quality of life, especially in the learning process at school. Dysmenorrhea management can be done in various ways, one of which is through acupressure therapy. Acupressure is a therapy that is easy to learn and has minimal side effects. This study aims to determine the effect of acupressure on dysmenorrhea in adolescents. The research method involves a literature review referring to the issues, methodology, and common results obtained. There are five articles that meet the criteria for review. Data searches consist of articles from national journals within the range of 2020–2025. The results show that the pain scale range after acupressure on adolescents experiencing dysmenorrhea decreased, with the average pain scale moving from moderate to mild.